2021
DOI: 10.1002/anie.202016089
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Near‐Infrared Electrofluorescence from a Thermally Activated Delayed Fluorescence Molecule

Abstract: Near-IR organic light-emitting diodes (NIR-OLEDs) are potential light-sources for various sensing applications as OLEDs have unique features such as ultraflexibility and low-cost fabrication. However, the low external electroluminescence (EL) quantum efficiency (EQE) of NIR-OLEDs is a critical obstacle for potential applications. Here, we demonstrate a highly efficient NIR emitter with thermally activated delayed fluorescence (TADF) and its application to NIR-OLEDs. The NIR-TADF emitter, TPA-PZTCN, has a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 46 publications
(64 reference statements)
0
93
0
Order By: Relevance
“…In 2019, Zhang et al 111 reported a red TADF emitter based on an acceptor PZCN, achieving a high EQE of 27.4% at 628 nm in the doped device, and the non‐doped device exhibited EQE of 5.3% with an NIR EL at 680 nm. Recently, by using a similar structure to TPA‐PZCN but with stronger electron‐withdrawing ability via two additional CN groups on the acceptor segment, TPA‐PZTCN exhibits more intense NIR EL with EQE max of 13.4% at 734 nm, and a long device operational lifetime (LT 95 ) of 168 h 112 . In 2020, Zhao et al 113 found that the rational molecular packing mode in the neat film can efficiently suppress the exciton quenching and improve the carrier transport.…”
Section: Fundamental Principle and Working Mechanismmentioning
confidence: 99%
“…In 2019, Zhang et al 111 reported a red TADF emitter based on an acceptor PZCN, achieving a high EQE of 27.4% at 628 nm in the doped device, and the non‐doped device exhibited EQE of 5.3% with an NIR EL at 680 nm. Recently, by using a similar structure to TPA‐PZCN but with stronger electron‐withdrawing ability via two additional CN groups on the acceptor segment, TPA‐PZTCN exhibits more intense NIR EL with EQE max of 13.4% at 734 nm, and a long device operational lifetime (LT 95 ) of 168 h 112 . In 2020, Zhao et al 113 found that the rational molecular packing mode in the neat film can efficiently suppress the exciton quenching and improve the carrier transport.…”
Section: Fundamental Principle and Working Mechanismmentioning
confidence: 99%
“…9 Very recently, Adachi et al applied a tetracarbonitrile unit (PZTCN) for the construction of TADF material (TPA-PZTCN) and achieved NIR emission at 734 nm with an EQE of 13.4%. 10 The intrinsic emission of TPACNBz and TPA-PZTCN in toluene was 674 nm. Remarkably, Qiao and coworkers reported a NIR-II TADF emitter (TPAAZ) with EL emission at 1010 nm by virtue of intermolecular charge-transfer aggregates (CTAs).…”
Section: Introductionmentioning
confidence: 98%
“…Organic light-emitting diodes (OLEDs) have been attracting great interests for their wide application in full color displays and lighting devices. [1][2][3][4][5][6][7][8][9][10][11][12][13] However, scarcity of efficient and stable blue emitters is still the bottle-neck for the development of OLEDs. Blue phosphorescent materials and thermally activated delayed fluorescence (TADF) materials can theoretically acquire 100% internal quantum efficiency (IQE) by harvesting both singlet and triplet excitons and they are so far the most practical and most promising materials, respectively.…”
Section: Introductionmentioning
confidence: 99%